Perlindungan Data Pribadi dalam Penyelenggaraan Pemilu: Tantangan dan Tawaran - Muhammad Alfian Kusnaldi; Nadira Fadila Syani; Yukiatiqa Afifah (Lex Renaissance, 2022)
The development of digital technology provides efficiency in all lines of life, including in the administration of elections. This spirit was later adopted by the General Elections Commission (KPU) by collecting the voters’ personal data and providing information about the election. However, in addition to providing convenience, the use of this technology also come with its own challenges, such as the leakage of election participants’ personal data. In this regards, the DPR has passed Law Number 27 of 2022 on Personal Data Protection (UU PDP). Therefore, legal protection is needed for the protection of the personal data of election participants in 2024. The problems that will be examined in this paper are the challenges faced by the KPU in protecting the personal data of election participants and forms of legal protection for the personal data of election participants in 2024. The method used in this writing is normative juridical by analyzing the PDP Law and collecting literature and literature review. The results in this study conclude that there are 3 challenges faced by the KPU before the PDP Law was passed, which are: the data scattered at every stage of the election administration; the regulations that have not been maximized; and the personal data protection literacy has not become knowledge and awareness among voters, organizers, data participants. Meanwhile, legal protection for the personal data of election participants in 2024 is carried out through PKPU No. 6 of 2021 and the PDP Law.Keywords: Legal Protection, Personal Data, Elections AbstrakPerkembangan teknologi digital memberikan efisiensi di segala lini kehidupan, termasuk dalam penyelenggaraan pemilu. Semangat tersebut kemudian diadopsi oleh Komisi Pemilihan Umum (KPU) dengan cara mengumpulkan data pribadi pemilih dan memberikan informasi seputar pemilu. Namun penggunaan teknologi ini di samping memberikan kemudahan juga memberikan tantangan tersendiri, seperti kebocoran data pribadi peserta pemilu. Lebih lanjut, DPR sudah mengesahkan UU Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi (UU PDP). Oleh karena itu diperlukan perlindungan hukum terhadap perlindungan data pribadi peserta pemilu 2024. Adapun permasalahan yang akan dikaji dalam tulisan ini adalah tantangan yang dihadapi oleh KPU dalam melindungi data pribadi peserta pemilu dan bentuk perlindungan hukum terhadap data pribadi peserta pemilu 2024. Metode yang digunakan dalam penulisan ini adalah yuridis normatif dengan menganalisis UU PDP dan mengumpulkan bahan literatur serta kajian pustaka. Hasil dalam penelitian ini adalah terdapat 3 tantangan yang dihadapi oleh KPU sebelum disahkan UU PDP, yakni data yang berserakan di setiap tahapan penyelenggaraan pemilu, peraturan yang belum maksimal, literasi perlindungan data pribadi belum menjadi pengetahuan dan kesadaran di antara pemilih, penyelenggara, data peserta. Sementara itu, prlindungan hukum terhadap data pribadi peserta pemilu tahun 2024 dilaksanakan melalui PKPU No 6 Tahun 2021 dan UU PDP. Kata-kata Kunci: Perlindungan Hukum, Data Pribadi, Pemilu